Nosology and classification of genetic skeletal disorders: 2019 revision. Issue 12 (21st October 2019) - Mortier, Geert R.; Cohn, Daniel H.; Cormier‐Daire, Valerie; Hall, Christine; Krakow, Deborah; Mundlos, Stefan; Nishimura, Gen; Robertson, Stephen; Sangiorgi, Luca; Savarirayan, Ravi; Sillence, David; Superti‐Furga, Andrea; et al.
Abstract: The application of massively parallel sequencing technology to the field of skeletal disorders has boosted the discovery of the underlying genetic defect for many of these diseases. It has also resulted in the delineation of new clinical entities and the identification of genes and pathways that had not previously been associated with skeletal disorders. These rapid advances have prompted the Nosology Committee of the International Skeletal Dysplasia Society to revise and update the last (2015) version of the Nosology and Classification of Genetic Skeletal Disorders. This newest and tenth version of the Nosology comprises 461 different diseases that are classified into 42 groups based on their clinical, radiographic, and/or molecular phenotypes. Remarkably, pathogenic variants affecting 437 different genes have been found in 425/461 (92%) of these disorders. By providing a reference list of recognized entities and their causal genes, the Nosology should help clinicians achieve accurate diagnoses for their patients and help scientists advance research in skeletal biology.